Narcissistic Mothers in Modernist Literature: New Perspectives on Motherhood in the Works of D.H. Lawrence, James Joyce, Virginia Woolf, and Jean Rhys - Rademacher, Marie Géraldine (transcript, 2019)
Narcissistic mothers are an important motif in modernist literature. Tracing its appearance in the works of writers such as D.H. Lawrence and Virginia Woolf, this book questions the dichotomous image of either benevolent or suffocating mother, which has pervaded religion, art and literature for centuries. Instead of focusing on the mother-child dyad as characterized primarily by maternal domination and the child' s submission, Marie Géraldine Rademacher insists on the definitional nuances of the term »narcissism« and considers the political and socio-economic context of the time in shaping these women's narcissistic behavior. The study thus inspires a more positive (re)reading of the protagonists.